Sulla (Hedysarum coronarium L.): A Sustainable Legume Specie Used for Forage in the Agroecological Living Landscape of Tunisia - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2022)
Sulla (Hedysarum coronarium L.): A Sustainable Legume Specie Used for Forage in the Agroecological Living Landscape of Tunisia.